2008
DOI: 10.1038/nm1752
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neurons implanted into people with Parkinson's disease survive without pathology for 14 years

Abstract: Postmortem analysis of five subjects with Parkinson's disease9-14 years after transplantation of fetal midbrain cell suspensions revealed surviving grafts that included dopamine and serotonin neurons without pathology. These findings are important for the understanding of the etiopathogenesis of midbrain dopamine neuron degeneration and future use of cell replacement therapies.Despite indirect evidence of long-term survival of fetal midbrain dopamine cell suspensions in people with Parkinson's disease 1 , the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
284
1
10

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(312 citation statements)
references
References 13 publications
17
284
1
10
Order By: Relevance
“…To date, immunohistochemical analysis of transplants surviving longer than 10 years has been reported for 5 cases [20,21,[25][26][27]. Consistent with the imaging data, these transplants that had survived for as many as16 years in the brain contained large numbers of dopaminergic neurons (Fig.…”
Section: Can Neural Grafts Survive and Provide Long-term Function?supporting
confidence: 72%
See 1 more Smart Citation
“…To date, immunohistochemical analysis of transplants surviving longer than 10 years has been reported for 5 cases [20,21,[25][26][27]. Consistent with the imaging data, these transplants that had survived for as many as16 years in the brain contained large numbers of dopaminergic neurons (Fig.…”
Section: Can Neural Grafts Survive and Provide Long-term Function?supporting
confidence: 72%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…Following a series of transplantation of cells from human fetal ventral mesencephalon into the striatum of PD patients, where the implanted cells developed Lewy bodies, (211)(212)(213)(214)(215), it was suggested that α-syntrophin can act in a prion-like fashion (100,216). A prion is an abnormally folded protein propagating by transmitting a misfolded state by acting as a template to guide misfolding of more proteins into prion form, typically tightly packed β-sheets.…”
Section: Pd As a Prion Diseasementioning
confidence: 99%
“…These studies resulted in no or minor improvements in the intervention groups, and to development of graft-induced dyskinesia in a sub-group of patients (234,235). Despite initial success, successful grafting and release of dopamine from the grafted cells for more than a decade, the implanted neurons developed Lewy bodies and were prone to cell death in similar ways as the endogenous dopaminergic cells in the SNpc, demonstrating that the disease can propagate from host to graft cells (211)(212)(213)215). These observations highlight the importance of understanding the underlying mechanisms responsible for the selective vulnerability of these cells in order to develop a therapy that halts the progression of the disease.…”
Section: Current Treatmentmentioning
confidence: 99%
“…Human dopamine cells transplanted and examined postmortem more than a decade after transplant show extensive reinnervation in the putamen [59,61,62,63]. In a small percentage of cells in some centers [61,62], but not others [63], cytoplasmic inclusions resembling Lewy bodies have been observed. Because the overall quality of the dopamine cell transplant and fiber outgrowth remains excellent, the significance of this rare observation is uncertain.…”
Section: Human Dopamine Neurons Survive Indefinitely Without Immunosumentioning
confidence: 99%